Христо Ботев: канонизиране и комерсиализиране на образа - Алексиева, Анна (Slavica Lodziensia, 2019)
The paper is focused on the history of the ideological unification of the image of Hristo Botev, when a monolith biography of him was forged from numerous diverse narratives about his life. That canonical narrative was smooth and not contradictory. During 20-ties and 30-ties of XX c., when nationalism was rising into trendy social movement, the image of Botev was sanctified, sharing a row with Vasil Levsky and becoming a leading figure in Bulgarian national heroic pantheon. With his affirmation as a national emblem, Botev‘s image became the subject of commercial uses, which are considered using the concepts of „consumerist nationalism” (B. Penchev) and “consumption of identity” (Anne-Marie Thiesse). During the years of socialism Botev was present in a consumer culture that functioned as utopia for future prosperity beyond any economic logic. The national hero can be seen as connected to that utopia, while reading the books of impressions in the “Hristo Botev” National Museum in the town of Kalofer, where he was born. Visitors also show disappointment with the promised, but unrealized socialist prosperity. In post-socialist years the image of Botev falls into a conglomerate of Euro-centric, nationalistic, nostalgic-communist and commercial manifestations.